Diet Modification and Metformin Have a Beneficial Effect in a Fly Model of Obesity and Mucormycosis - Shirazi, Fazal; Farmakiotis, Dimitrios; Yan, Yuanqing; Albert, Nathaniel; Kim-Anh, Do; Kontoyiannis, Dimitrios P. (PLOS ONE, 2014)
In an experimental model of obesity and hyperglycemia in Drosophila melanogaster we studied the effect of diet modification and administration of metformin on systemic infection with Rhizopus, a common cause of mucormycosis in diabetic patients. Female Wt-type Drosophila flies were fed regular (RF) or high-fat diet (HFD; 30% coconut oil) food with or without metformin for 48 h and then injected with R. oryzae. Survival rates, glucose and triglyceride levels were compared between 1) normal-weight flies (RF), 2) obese flies (HFD), 3) obese flies fed with RF, 4) flies continuously on HFD + metformin, 5) flies fed on HFD + metformin, then transferred to RF, and 6) obese flies administered metformin after infection. Glucose levels were compared across groups of non-infected flies and across groups of infected flies. Survival was significantly decreased (P = 0.003) in obese flies, while post-infection glucose levels were significantly increased (P = 0.0001), compared to normal-weight flies. Diet and administration of metformin led to weight loss, normalized glucose levels during infection, and were associated with decreased mortality and tissue fungal burden. In conclusion, diet and metformin help control infection-associated hyperglycemia and improve survival in Drosophila flies with mucormycosis. Fly models of obesity bear intriguing similarities to the pathophysiology of insulin resistance and diabetes in humans, and can provide new insights into the pathogenesis and treatment of infections in obese and diabetic patients.